What strategies do cardiologists employ for heart failure management? Insights from Indian clinical practice - Khobragade, Kunal; Kumar, Neeraj (International Journal of Research in Medical Sciences, 2024)
Background: Heart failure (HF) is a leading cause of morbidity and mortality in India, with ischemic heart disease (IHD) being a primary contributor, particularly in patients with reduced ejection fraction (HFrEF). Despite comprehensive guidelines, a gap exists between guideline-directed medical therapy (GDMT) and real-world practices. Methods: A cross-sectional survey of 476 cardiologists across India was conducted from April to June 2023 to evaluate current therapeutic approaches for managing HFrEF. The study assessed alignment with established guidelines, including the American college of cardiology/American heart association (ACC/AHA) recommendations. Results: HFrEF accounted for 40-60% of HF cases, typically diagnosed at advanced stages New York heart association (NYHA class III), with EF often reduced to 20-30%. While 94.5% of cardiologists supported NT-proBNP testing for HF management and 73.5% endorsed ARNi as first-line therapy, ARNi usage remained suboptimal at 20-60%. Most cardiologists (67%) preferred initiating quadruple therapy within 12-24 weeks of diagnosis, citing medication tolerance as a key barrier to achieving optimal treatment goals. Conclusions: This study highlights substantial gaps in the adoption of guideline-recommended therapies for HFrEF in India. Improved strategies are needed to address barriers to GDMT implementation and ensure timely interventions to enhance patient outcomes.